ANALISIS NILAI MORAL DALAM FILM NEGERI 5 MENARA YANG DIADAPTASI DARI NOVEL KARYA A. FUADI - Selviani Meida Putri; Ika Mustika; Agus Priyanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Regarding moral values in the film titled "Negeri 5 Menara" by director Affandi Abdul Rachman adapted from the novel by A. Fuadi. the researcher analyzes the moral values told in the film. This research can be useful for readers because there are many messages we can take about moral values in the film. The research method used is to use the library research method to analyze the film. The results of research that has been carried out on the film are moral values including surrender or trust, discipline, hard work, responsibility, mutual respect, help and be grateful. Through the research process, the researcher seeks to integrate good moral values so that the objectives to be conveyed can be understood by the reader. Thus it can be concluded that the film titled "Negeri 5 Menara" is suitable to be a good spectacle for all people. Be it ordinary people, or intellectuals. Parents or teenagers can enjoy it.